TIG melted surface modified titanium alloy for automotive cylinder liner application - Adelek, S.A.; Maleque, Md. Abdul (Aybil Dijital Baskı Sistemleri ve Matbaa Hizmetleri, 2014)
Tungsten inert gas (TIG) surface modification with Fe-based alloy can give protection against wear and corrosion of metallic component material. In this study, an attempt has been made to explore deposition of Fe-based alloy on commercial purity titanium (CP-Ti) by TIG torch melting process to improve resistance of substrate to wear and corrosion. Three different powder blends with nominal composition of 97Fe2C1Si, 94Fe 4C2Si and 91Fe6C3Si were separately melted on CP-Ti using a conventional TIG welding torch produced at 100 A and energy input 1350 J/mm. Analysis of the results showed that TIG torch produced melt pools geometry with good metallurgical bonding with the substrate. The melt microstructures consisted of variety of different TiC precipitates. Pores were conspicuously seen on the melt microstructure modified with highest carbon content. Both microhardness and wear resistance showed a significant improvement particularly after TIG coating with 94Fe4C2Si. Thus, it appears that an optimized composition of TIG coated with 94Fe4C2Si was best to control abrasive resistance and for the application of cylindrical liner.